Acute echocardiographic and electrocardiographic effects of triggered left ventricular pacing - Pfeffer, Tobias Jonathan; Neuser, Jonas; Mueller-Leisse, Johanna; Hohmann, Stephan; Duncker, David; Bauersachs, Johann; Veltmann, Christian; Berliner, Dominik (PLOS ONE, 2022)
Cardiac resynchronization therapy (CRT) is an essential pillar in the therapy of heart failure patients with reduced ejection fraction (HFrEF) presenting with broad left bundle branch block (LBBB) or pacemaker dependency. To achieve beneficial effects, CRT requires high bi-ventricular (BiV) pacing rates. Therefore, device-manufacturers designed pacing algorithms which maintain high BiV pacing rates by a left ventricular (LV) pacing stimulus immediately following a right ventricular sensed beat. However, data on clinical impact of these algorithms are sparse. We studied 17 patients implanted with a CRT device providing triggered left ventricular pacing (tLVp) in case of atrioventricular nodal conduction. Assessment of LV dyssynchrony was performed using echocardiographic and electrocardiographic examination while CRT-devices were set to three different settings: 1. Optimized bi-ventricular-stimulation (BiV); 2. Physiological AV nodal conduction (tLVp-off); 3. Physiological AV nodal conduction and tLVp-algorithm turned on (tLVp-on). QRS duration increased when the CRT-device was set to tLVp-off compared to BiV-Stim, while QRS duration was comparable to BiV-Stim with the tLVp-on setting. Echocardiographic analysis revealed higher dyssynchrony during tLVp-off compared to BiV-Stim. TLVp-on did not improve LV dyssynchrony compared to tLVp-off. QRS duration significantly decreased using tLVp-algorithms compared to physiological AV nodal conduction. However, echocardiographic examination could not show functional benefit from tLVp-algorithms, suggesting that these algorithms are inferior to regular biventricular pacing regarding cardiac resynchronization. Therefore, medical treatment and ablation procedures should be preferred, when biventricular pacing rates have to be increased. TLVp-algorithms can be used in addition to these treatment options.